Life On Planets Other Than Earth From The Perspective Of The Qur’an Surat An-Nahl Verse 49 - Muhammad Akmansyah; Sovia Mas Ayu; Asmara Dewi; Eka Wahyu Safitri (Proceeding International Conference on Religion, Science and Education, 2023)
The background of this research is that life is not an absolute thing that only planet Earth has. In the mid-20th century, the search for life on planets other than Earth began to be encouraged. There are a number of Muslims who quickly legitimize the verses of the Qur’an against the existence of life on planets other than earth. The formulation of the problem from this research is how life is on planets other than Earth from the perspective of science and Qs. Al-Nahl verse 49? And what is the relevance between science and the Koran regarding life on planets other than Earth? This study aims to determine the perspective of science and Al-Qur’an Surah Al-Nahl verse 49 about life on planets other than Earth. The type of research that the writer uses is library research which is descriptive and analytical. Content analysis and interpretation are used to analyze the data in this study. Life on the planets of the solar system that are currently found are still in the form of microorganisms, such as the ALH84001 fragment on the meteor planet Mars, and it is suspected that there is life in the solar system on the planet Venus, the satellite Io and also Europa. Because these planets and satellites found water in liquid form. The Qur’an gives a hint to the letter Al-Nahl verse 49 with the word dabbah which means reptiles that exist on earth and in samawat (sky). Based on the results of the research and analysis, it can be concluded that there is relevance between science and the Koran regarding life on planets other than Earth. This is demonstrated by the discovery of microorganisms on Mars and water. Surah Al-Anbiya verse 30 also states that water is the main source for forming life, so the discovery of water on the ancient planets Venus, and Mars, the satellite Io, and Europa, and the word dabbah in Surah Al-Nahl verse 49 is proof that there is no dichotomy between science and al- -Quran.